Private investment, R&D and European Structural and Investment Funds: Crowding-in or crowding-out? - Roberto A. De Santis; Francesca Vinci (European Central Bank (ECB), 2025)
We employ a novel regional dataset on European private investment and business R&D spanning the years 2000 to 2021, along with comprehensive historical data on European Union Structural and Investment (ESI) funds, to estimate whether ESI funds have crowding-in or crowding-out effects on private investment and business R&D. Our analysis, leveraging regional variation and a fiscal instrument immune to region-specific shocks, reveals a significant crowding-in effect, with 1 euro in ESI funds increasing private investment by 1.1 euros and business R&D by 0.1 euros after two years. The effect is stronger in developed regions for private investment and in less developed regions for R&D. Additionally, crowding-in effects are stronger in regions where corporate private debt is relatively higher. Among the different ESI funds, the Cohesion Fund (CF) shows the largest estimated impact, while the European Regional Development Fund (ERDF) yields somewhat smaller but statistically more robust results.
Keywords: E22; H54; O38; O52; R11; R58; 330; EU; Structural and Investment Funds; Private Investment; R&D; fiscal instruments